Application of Design of Experiments for development of a downstream process of an antimicrobial peptide expressed as a fusion protein in E. coli - Jasmin Ganczarski (2024)
The excessive use of antibiotics is increasingly leading to the formation of resistance, which will cause into a global crisis. The requirement for potential alternative therapeutics is therefore becoming increasingly important. Natural antimicrobial peptides (AMPs), which already serve as host defense peptides in the immune system of various organisms, are highly promising candidates. However, the biopharmaceutical development and production of AMPs is seen as a major challenge. The specific properties of the AMP, the choice of the expression system and the design of the plasmid require specific process developments until a pure form of the desired AMP is finally available. In this work, a downstream process has been developed to obtain the AMP NK2-ALK, which was expressed as a fusion construct in E. coli. The fusion construct is predominantly present as insoluble inclusion bodies (IBs). The aim was to maximize the product amount of fusion construct in the purest possible state. The process development was carried out using the Design of Experiments (DoE) strategy, which enabled the screening of significant process parameters and the definition of optimal working ranges. A high-pressure homogenizer was used for cell disruption and the released IBs were washed and solubilized. The final purification of the fusion construct was carried out using ion immobilized affinity chromatography (IMAC). Coomassie blue staining showed that the fusion construct exhibited a high degree of purity after the downstream process. The imidazole concentration in the binding buffer (10 mM) and in the elution buffer (300-500 mM) were determined as significant process parameters. The addition of NaCl (1 M) was also determined as a relevant factor.